(3GdaJGhi GdJGJGQNGfjIs - (3YGde Hf YdGA GdMfaj,J (B286 (3g` s
(3ChdgG (B:s
(3fMeOc QHfG Ydi eG CSHZ YdjfG ef GdYWGA CeG HYO abO CTGQ Edi ef ETGQJg hWGYJg Zfe Cf CgJe HLejY cJGH LGeY ddaJGhi hGdhGbYGJ , MGh ddCMcGe hGdQhGjGJ hSejJg HGdaJGhi GdJGJGQNfjI s
(3BNQgG (B:s
(3aONd GdNJf GdEUWHd ai djdI eXdeI djNQL MeGQg ahVY jOg Ydi GdHbQ ai XdeI Gddjd jMfK ai jejfg hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddCHhGHs
(3HgG fXGe GdJYbjHIs
(3GdejcQhajde Ydi YdHJjf s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3Gdabg GdESdGejs